THE INFLUENCE OF YOUTUBE CONTENT ON MOBILE LEGENDS ON THE INTEREST IN E-SPORTS TOURNAMENTS AMONG ADOLESCENTS IN JAGAKARSA, SOUTH JAKARTA - Gusrialdi, Joko; Kau Suni, Eugenius (Transpublika Publisher, 2024)
Today's technology is getting more advanced and sophisticated with smartphones that can be applied easily anytime and anywhere. Having a smartphone makes it easier to get trending information. There are several examples of social media applications that are in great demand, such as Instagram, WhatsApp, Line, Twitter, YouTube, and others. Most people in the world use YouTube to share their videos or just enjoy various video clips. This study aims to describe interest in participating in E-sports tournaments after watching YouTube mobile legends content. Knowing the influence of YouTube mobile legends content on interest in E-sports tournaments in Jagakarsa youth, South Jakarta. The method used in this research is quantitative by involving teenagers in Jagakarsa, South Jakarta who play mobile legends games and are active in the mobile legends community. The data collection process uses a questionnaire that is distributed via the Google Form link and then processed using a simple linear analysis technique. The results of the study show that Youtube Mobile Legends content has a significant influence on adolescents in Jagakarsa, South Jakarta. It can be concluded that Mobile Legends content has a positive and significant influence on interest in tournaments among young people in Jagakarsa, South Jakarta. Obtaining these results is dominantly influenced by the Cognitive effect dimension as the highest measure of variable X (Influence of Mobile Legends Content) with the indicator: Motivated to Play the Mobile Legends Game.